Pengaruh Strategi Pembelajaran React dan Berpikir Kreatif terhadap Kemampuan Komunikasi Matematis Siswa di Smpn 205 Jakarta - Ilham Jaya; Abid Marzuki (Bima Journal of Elementary Education, 2023)
The Purpose of this research is to know the influence of learning strategy REACT on students' mathematical comunication ability. This research was conducted at SMPN 205 Jakarta. The research design used is treatment by level 2x2, with independent ariable is learning strategy that is REACT and expository, dependent ariable is mathematical communication ability, and moderator ariable is creative thinking. Sampling technique used cluster random sampling. The result of this research is first learning is REACT effecti e to impro e student communication ability so that this strategy can be used by junior high school teacher in the matter of building rectangle flat. Second, the learning effect on students 'mathematical communication ability depends on the students' creative thinking level. Third, with learning strategy REACT students who ha e a level of creative thinking high scores ha e higher mathematical communication skills compared with expository learning